Soilless Culture, Growing Media and Horticultural Plants - Gruda, Nazim; Jackson, Brian Eugene (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint showcases a collection of a Special Issue entitled "Soilless Culture, Growing Media and Horticultural Plants". Within its pages, readers will find an assortment of 22 original papers accompanied by 1 review paper and 1 editorial. Representing a collaborative effort involving by 84 authors from 15 different countries, this Special Issue explores cutting-edge advancements in soilless culture, investigating the interaction between soilless and environmental factors while also exploring their consequential impacts on plant growth and physiology. Additionally, these studies meticulously scrutinize the accumulation of secondary metabolites. The compositions of nutrient solutions and the physical attributes of substrates and mixtures are illuminated through rigorous analyses. Furthermore, a spotlight is placed on the dynamic interactions between microorganisms and plant-growing media. In the near future, climate change and environmental and ecological issues will steer the trajectory of soilless culture systems and the choice of growing media constituents.